Tanggung Jawab Negara terhadap Pelarangan Menyeluruh Ranjau Anti-Personel di Indonesia dalam Konflik Bersenjata di Aceh - Muhammad Heikal Daudy (Kanun Jurnal Ilmu Hukum, 2013)
ABSTRACT: Convention on the Total Prohibition of Anti-Personnel Mines, was formed with a view to realizing the "Free Mine World ". Indonesia has ratified the convention, commonly known as the Ottawa Convention 1997 to the Undang-Undang Nomor 20 Tahun 2006. As a State Party, Indonesia is obliged to fulfill all the provisions of the convention and the most important is the commitment to protect every citizen from falling victim to anti-personnel mines. In armed conflict of Aceh, mines were used by both parties that the Government of the Republic of Indonesia and the Free Aceh Movement, indications are casualties is dominated by civilians after the armed conflict stopped. For these reasons, the parties are considered not to comply and execute its responsibility of each as intended conventions and International Humanitarian Law Principles. The reality is stands to reason, because the implementation of the state responsibility principle for the total prohibition anti-personnel mines are less than the maximum and seemed to slow. The problem lies in the lack of political will of both parties to keep the peace and support the development agendas in Aceh on going basis, especially with completing problems arising from the existence of anti-personnel mines. State Responsibility Towards a Total Prohibition Anti-Personnel Mines in Indonesia in Armed Conflict of Aceh